2019
DOI: 10.3390/e21020213
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Rate-Distortion Analysis of Symmetric Remote Gaussian Source Coding: Centralized Encoding vs. Distributed Encoding

Abstract: Consider a symmetric multivariate Gaussian source with ℓ components, which are corrupted by independent and identically distributed Gaussian noises; these noisy components are compressed at a certain rate, and the compressed version is leveraged to reconstruct the source subject to a mean squared error distortion constraint. The rate-distortion analysis is performed for two scenarios: centralized encoding (where the noisy source components are jointly compressed) and distributed encoding (where the noisy sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…for any cover S of {1, · · · , L}. A result by Zamir and Berger [21] (see also [22] for a related result) indicates that…”
Section: Problem Definition and Main Resultsmentioning
confidence: 95%
“…for any cover S of {1, · · · , L}. A result by Zamir and Berger [21] (see also [22] for a related result) indicates that…”
Section: Problem Definition and Main Resultsmentioning
confidence: 95%
“…4 proves the accuracy of Algorithm 1 showing the similar quantity compared to the pdepe Toolbox of MATLAB. In addition, it is revealed that our scheme has an outperformance over the online/offline algorithms proposed in [25], [26]. We also define the accuracy as := 1 −…”
Section: Lemma 1: Smfg Is Completely Written By An Integration Of Hjbmentioning
confidence: 95%
“…One can get the Volume-Entropy over the two given Entangled-Spheres 22 B i and B j as the maximal exponential growth rate of the volume of the metric ball B i,j (located in the entangled region). 23 The Volume-Entropy of the Graph in accordance with the aforementioned Riemann-Sphere is expressed 24 as Max 25 Step 2: Transfer-Entropy Let us investigate the correlation-coefficient 26 of each pair of (X , W) and (Y, W) as well. This requires the Markov chains X • U 1 • W and Y • U 2 • W, respectively, given the correlated parts U 1 and U 2 .…”
Section: Appendix B Proof Of Lemmamentioning
confidence: 99%
“…This book, composed of the collection of papers that have appeared in the Special Issue of the Entropy journal dedicated to “Information Theory for Data Communications and Processing”, reflects, in its eleven chapters, novel contributions based on the firm basic grounds of information theory. The book chapters [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] address timely theoretical and practical aspects that carry both interesting and relevant theoretical contributions, as well as direct implications for modern current and future communications systems.…”
mentioning
confidence: 99%
“…This book focuses on timely and relevant features, and the contributions in the eleven book chapters [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], summarized below, address the information theoretical frameworks that have important practical implications.…”
mentioning
confidence: 99%